Moving away from disproportionate exclusionary discipline: developing and utilizing a continuum of preventative and instructional supports. Issue 4 (2nd August 2021) - Nese, Rhonda N. T.; Nese, Joseph F. T.; McCroskey, Connor; Meng, Paul; Triplett, Danielle; Bastable, Eoin
Abstract: Ample scientific research has documented that exclusionary discipline practices are both ineffective for reducing unwanted behaviors and harmful to the long-term social and academic outcomes of students. Further, exclusionary discipline practices are especially harmful given their disproportionate use with students of color, students with disabilities, students living in poverty, and students who are struggling academically. To address these issues, the authors describe a process that uses instructional strategies as alternatives to exclusion. These instructional strategies hold promise for reducing the use of disproportionate discipline, improving student behavior and social skills, and strengthening student–teacher relationships.